(untitled) (Eurasian Journal of Philology Science and Education, 2018)
Categories of name words in Old Kipchak Language The article focused on research about the categories of the name words in Old Kipchak language. The materials taken for the analysis would be the creation of the name words in Old Kipchak language by the lexical, morphological and syntactic ways. During the analysis of the material, the author cites the difference between the main root and the derivative root on the identity of the name words in the ancient language of Kipchak and the lack of the different grammatical applications